DOMINANT FACTOR OF DECREASE OF STUDENT LEARN MOTIVATION IN AKES RAJEKWESI BOJONEGORO IN YEAR 2014 - RAHMAWATI, RAHMAWATI (Asuhan Kesehatan : Jurnal Ilmiah Ilmu Kebidanan dan Keperawatan, 2014)
Nursing Diploma program is a study program  that focuses on the skills that are competent in providing nursing care to patients. In connection with this, it is very important for all students to follow lectures and practical activities that will prepare students as competent nurses in performing the task and ready to work as a nurse. The low student motivation to learn is often regarded as the cause of the poor quality of college graduates due to low motivation does not allow students to have a good mastery of the learning materials. The purpose of this study is to find the dominant factor decrease of student learn motivation in  Nursing Diploma program   Akes Rajekwesi Bojonegoro 2014.         The study design was a descriptive with survey approach. Samples were taken by purposive sampling technique, in DIII  Nursing program students who have high levels of absenteeism at least 2  lectures by> 10%. Instrument research using questionnaires with a single variable that is the dominant factor decrease of student learn motivation. Processing data using scoring to find the dominant factor and presented in tabular form.       The results showed that the dominant factor decrease of student learn motivation in Nursing Diploma program of Akes Rajekwesi Bojonegoro  2014 was feeling less capable in the academic field (36%), lecture by the will of the parents (40%), solid schedule (64%) and environmental influences (36%)        Problem of a lack of motivation on student need serious attention and needs to be pursued actions that support such involvement is more intensive academic counselors and the active role of guidance counseling. Key Word : Dominant factor, Learn motivation